Linking surface pCO2 variability to physical processes along a continental shelf–ocean transect in the southwestern Atlantic Ocean during austral autumn and winter - Albuquerque, Cíntia; Miguel, Gizyelle; Lencina-Avila, Jannine M.; Pinho, Luana; Marotta, Humberto; Fernandes, Alexandre Macedo; Passos, Elisa Nóbrega; Amora-Nogueira, Leonardo; Campos, Edmo; Cotrim da Cunha, Leticia (Frontiers in Marine Science, 2025)
The southwestern South Atlantic Ocean is an important global sink of atmospheric carbon dioxide (CO2), driven by increased primary productivity in a nearby region where oligotrophic warm currents converge with nutrient-rich cold waters. However, uncertainties remain regarding CO2 dynamics and the role of physical processes in CO2 uptake across this region. Here, we assess variations in surface partial pressure of CO2 (pCO2) and air–sea CO2 fluxes in the Southwest Atlantic, along a transect from the continental shelf to the open ocean at 34.5°S during austral autumn 2018 and winter 2019. High-resolution spatial measurements of the temperature, salinity, and molar fraction of surface CO2 were conducted. In autumn 2018, the shelf region acted as a source of CO2 to the atmosphere (median of 3.2 mmol CO2 m-2 d-1), which was partially offset by a sink (median of –2.5 mmol CO2 m-2 d-1) in the open ocean. In contrast, the entire transect in winter 2019 presented median CO2 emissions of 1.5 mmol CO2 m-2 d-1, which differs from climatological estimates. The spatial and seasonal variations in surface ocean pCO2 were linked to variable hydrodynamic processes, including water masses and mesoscale structures. Our findings reveal that, in one of the most productive oceanic waters worldwide, pCO2 may be influenced by distinct continental inputs (e.g., rivers, runoff, and groundwater discharge) and water masses (e.g., Tropical Water, Plata Plume Water and Subtropical Shelf Water). Therefore, the local hydrodynamic processes can modulate high spatial and seasonal variability in CO2 exchange at the ocean–atmosphere interface, with potential implications for regional and global carbon budgets. General results, such as climatological, cannot fully capture the influence of regional upwelling and continental water input, which highlights the importance of high-resolution regional observations.